Pattern of cervical disc changes in patients with non-traumatic neck pain: a review of cervical MRI scan findings - Gabkwet, Anthony E.; Igoh, Emmanuel O.; Gwom, Pam M.; Taiwo, Folake Y.; Salaam, Abdul J.; Danjem, Samuel M.; Pam, Stephen D. (International Journal of Advances in Medicine, 2021)
Background: Neck pain is a common global health problem causing significant individual disability and socioeconomic burden on health care facilities. Many factors have been associated with neck pain but the most implicated is the cervical intervertebral disc disease. Magnetic resonance imaging (MRI) scan is considered globally as the most sensitive test for detecting degenerative disc abnormalities associated with neck pain. The objective of this study was to evaluate cervical disc changes on MRI in non-traumatic symptomatic subjects and to accumulate baseline data on the pattern of changes. Methods: A four-years retrospective review of 115 patients (age range 13 to 81 years) who had a cervical MRI scan due to non-traumatic neck and radiating shoulder pain from September 2017 to February 2021 at the Radiology Department of Jos University Teaching Hospital North Central Nigeria. All the patients were scanned using a Single Siemens (Magnetom Concerto) MRI scanner with 0.2T magnetic field strength. Sagittal T1-weighted and T2-weighted fast spin-echo images were acquired, and axial images and contrast-enhanced studies were done only when required. Results: The study included 74 (64.3%) males and 41 (35.7%) females with a mean age of 50.7±13.2 and a modal age group of 41-60 years. The normal intervertebral disc was commonest at C2/C3 followed by C6/C7 level while degenerative disc changes were most commonly seen at C4/C5 followed by C5/C6 level. The majority (93%) of patients had multilevel intervertebral disc changes and the most frequent and severe occurrences of intervertebral disc dehydration, bulge, herniation, and disc space narrowing were noted at C4/C5 (79.1%), C4/C5 (12.2%), C5/C6 (59.1%) and C4/C5 (10.4%) respectively. Conclusions: This study found all patients examined had at least one level of intervertebral disc changes with the majority having multilevel involvement (93%). The most commonly and severely affected level was C4/C5 followed by C5/C6 level. The most frequent and severe occurrences of disc desiccation, bulge, herniation (protrusion/extrusion/sequestration) and disc height reduction were noted at C4/C5 (79.1%), C4/C5 (12.2%), C5/C6 (59.1%) and C4/C5 (10.4%) respectively.